Disulphide structure of high-molecular-weight (HMW-) gliadins as affected by terminators. (November 2017) - Schmid, Markus; Wieser, Herbert; Koehler, Peter
Abstract: This study aimed at elucidating SS-bonds of HMW-gliadins (HGL) from wheat with the focus on terminators of glutenin polymerisation. HGL from wheat flour extracts non-treated or treated with the S-alkylation reagent N-ethylmaleinimide (NEMI) were compared. HGL from wheat flour Akteur were isolated, hydrolysed with thermolysin and the resulting peptides pre-separated by gel permeation chromatography and analysed by liquid chromatography/mass-spectrometry using alternating electron transfer dissociation/collision-induced dissociation. Altogether, 22 and 28 SS-peptides from samples without and with NEMI treatment, respectively, were identified. Twenty-six peptides included standard SS-bonds of α- and γ-gliadins, high-molecular-weight and low-molecular-weight glutenin subunits. Eleven SS-bonds were identified for the first time. Fifteen peptides unique to HGL contained cysteine residues from gliadins with an odd number of cysteines (ω5-, α- and γ-gliadins). Thus, gliadins with an odd number of cysteines, glutathione and cysteine had acted as terminators of glutenin polymerisation. Decisive differences between samples without and with NEMI treatment were not obvious showing that the termination of polymerisation was already completed in the flour. The two HGL samples, however, were different in the majority of ten peptides that included disulphide-linked low-molecular-weight (LMW) thiols such as glutathione and cysteine with the former being enriched in the non-treated HGL-sample. Highlights: The disulphide structure of HMW gliadins from wheat flour has been analysed for the first time. Formation of HMW gliadins is already completed in the mature grain. Gluten proteins with an odd number of cysteine residues act as terminators. Low-molecular weight thiols modify the structure of HMW gliadins during extraction.